Relationship Between COVID-19 Infection and Liver Injury: A Review of Recent Data - Ali, Nurshad (Frontiers in Medicine, 2020)
The COVID-19 outbreak is a great threat to public health worldwide. Lung injury is the main outcome of COVID-19 infection; however, damage can occur in other organs including the liver. Currently, limited data are available that link underlying liver injury with the severe SARS-CoV-2 infection. This review summarizes the available data on liver test abnormalities in COVID-19 patients; critically evaluates the possible causes of liver injury and provides recommendations for clinicians. In laboratory tests, serum levels of liver test markers notably transaminase, gamma-glutamyl transferase and total bilirubin were significantly higher in severe patients with COVID-19 infection. The use of certain drugs especially lopinavir and ritonavir showed an association with the progression of liver damage in severe cases. Available data suggest that liver injury in COVID-19 patients may result from direct effect by the virus, immune-mediated inflammation or drug toxicity. Some studies demonstrated that COVID-19 patients with pre-existing liver disease are at higher risk for hospitalizations and mortality. Therefore, the impact of pre-existing liver disease on treatment and clinical outcomes of COVID-19 should be determined. Large-scale clinical studies are needed to identify the causes of liver injury in patients with COVID-19 infection.